Early childhood financial literacy: A systematic literature review - Pramitasari, Muktia; Siti Syarah, Erie; Risnawati, Erna; Shofiyah Tanjung, Khoiriyah (Aṭfālunā Journal of Islamic Early Childhood Education, 2023)
Financial literacy is important for individuals, society as a whole and contributes to economic growth and development. This systematic literature review aims to provide information regarding the importance of financial literacy for early childhood, financial literacy that early childhood can learn and good practices that have been implemented in stimulating early childhood financial literacy. This research reviews 14 journals from 143 various international journals and proceedings. Research has found that introducing the concept of financial literacy from an early age will encourage healthy financial habits in the future, financial education provides knowledge, skills and confidence, and various media and methods have been developed to stimulate early childhood financial literacy.